ChemInform Abstract: Modular Preparation of 5‐Halomethyl‐2‐oxazolines via PhI(OAc)2‐Promoted Intramolecular Halooxygenation of N‐Allylcarboxamides. Issue 15 (24th March 2016) - Liu, Gong‐Qing; Yang, Chun‐Hua; Li, Yue‐Ming
Abstract: Trimethylsilyl bromide and chloride give the respective 5‐bromo/chloro‐methyl‐2‐aryloxazolines in similar yields.